Solution of an inverse kinematics problem using dual quaternions - Chen, Lei; Zielińska, Teresa; Wang, Jikun; Ge, Weimin (Zielona Góra: Uniwersytet Zielonogórski)
The paper proposes a solution to an inverse kinematics problem based on dual quaternions algebra. The method, relying on screw theory, requires less calculation effort compared with commonly used approaches. The obtained kinematic description is very concise, and the singularity problem is avoided. The dual quaternions formalism is applied to the problem decomposition and description. As an example, the kinematics problem of a multi-DOF serial manipulator is considered. Direct and inverse kinematics problems are solved using division into sub-problems. Each new sub-problem proposed is concerned with rotation about two subsequent axes by a given amount. The presented example verifies the correctness and feasibility of the proposed approach.
Keywords: dual quaternions; kinematics; simulation; robotics; screw theory